If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -2(6) = 0 Multiply -2 * 6 -3 + -12 = 0 Combine like terms: -3 + -12 = -15 -15 = 0 Solving -15 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -2(x+6)+3x= | | 3x-10=5x+45 | | 6y=10x-4 | | 3x+2y=73 | | 5x-6+6x-8=x+4+x+10 | | x^2+8=-8x+1 | | 10x-7y=11 | | 600t^2+60t-3=0 | | 140=x^(1/2) | | 140=x^1/2 | | 6a-(4a+7)= | | 2(cos(2x))+2=0 | | 4y=-3x+2 | | 9(x+4)-6(x-2)=3(x+16) | | 7x=9-3(x-1) | | (x-3)2=(3x-5)2 | | (27.9-18.6)/3.1 | | 3.5=14 | | (x-3)-(5-3x)=2x(x+1) | | 6x-3+x-4=4x+5+3x | | 2x^2+(2-i)x+1=0 | | 25y^2-100x^2=0 | | v^2+2v+7=0 | | 5n^2=90-15n | | 35-2r=3r-5 | | z+3=29*2 | | 18-2x^2/9-3x | | -196=-9.8t^2 | | -1.8=-5x-8 | | 6x^2-5x-9=0 | | f(x)=8x+11 | | ln(9x^2-4)=6x+4 |